Identification and Biological Evaluation of Small Molecules as Sirtin Inhibitor against Breast Cancer : - Venkateswarlu, Kojja (IIT(BHU) Varanasi, 2026)
Abstract is available in the attachment.
Keywords: Pharmaceutical Engineering and Technology